Cyclic deformation behavior and fatigue lives of ultrafine-grained Ti-6AL-4V ELI alloy for medical use - Saitova, L. R.; Höppel, Heinz Werner; Göken, Mathias; Semenova, I. P.; Valiev, R. Z. (International Journal of Fatigue, 2009)
It was shown that introducing an ultrafine-grained (UFG) microstructure in pure metals as well as some alloys leads to strongly enhanced fatigue properties. The cyclic deformation behavior of UFG Ti-6Al-4V ELI (extra low interstitials) alloy is studied by both strain and stress controlled fatigue tests using plastic strain amplitudes between 3 x 10(-4) and 5 x 10(-3) and stress amplitudes ranging from 550 to 670 MPa. The UFG microstructures were obtained by equal channel angular pressing (ECAP) with different number of passes followed by a subsequent thermomechanical treatment (TMT). When compared to the conventional grain (CG) size counterpart, the UFG alloy exhibited a pronounced enhancement in the fatigue life in the S-N (Wohler) diagram. It was also shown that additional UFG processing prior to TMT did not result in any further improvement of the fatigue resistance. Furthermore, microstructural investigations revealed a high cyclic stability of the UFG microstructure. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Ti-6Al-4V; Ultrafine-grained material; Fatigue strength; S-N curves; Damage